Feed contaminants and anti doping tests - Bonnaire, Yves; Maciejewski, P; Popot, M.A; Pottin, S (MTT, 2008)
Pharmacologically active drugs are considered as prohibited at any concentration (with the exception of threshold drugs) in body fluids collected during racing or equestrian events, even if environmental or feeds contamination might occur. This can create unexpected positive cases when feeds or supplements contain unlisted drugs in supplements or in feeds containing alkaloids such as atropine, scopolamine or caffeine. There are several contamination origins depending on drugs involved. Manufacturing or transportation are major factors which may explain the presence of these drugs in the feed. Two studies were carried out to assess the maximum intake of major contaminants absorbed through the diet that would not result in a positive test in urine. Caffeine, theobromine, theophylline, atropine, scopolamine and morphine were administered orally at different dosages, for 2 days before urine was sampled and submitted to analysis by screening methods. Each cocktail of drugs were administered to two horses. Caffeine: a 10 mg daily intake was found to induce urinary concentrations ranged from 23 to 50 ng/ml; theobromine: a 30 mg daily intake was found to produce urinary concentrations from 700 to 900 ng/ml; theophylline: a 15 mg/day intake was found to induce urinary concentrations of 140-500 ng/ml; atropine: a 10 mg/day intake was found to produce 10 to 25 ng/ml in urine; scopolamine: a 10 mg/day intake was found to give urinary concentrations from 25-140 ng/ml and, finally morphine: a 1 mg/day intake was found to produce a range of 10-15 ng/ml in urine. Horse feeds containing contaminants, even at low levels, may produce positive test results in anti-- doping urine analysis. A maximum daily intake or a maximum concentration in feeds must be adopted to avoid inadvertent positive findings in routine tests. The use of feeds or supplements properly tested or guaranteed by manufacturers by an effective quality controlled process is crucial for feeding horses in training or before competition or racing events. The sensitivity of screening tests used to control feeds or feed supplements must at least comply with the concentrations determined in the present study. Nevertheless the lack of international harmonization remains an important issue, a MRL s (Maximum Residue Level) like approach would be the more appropriate as soon as harmonized levels of detection will be adopted.
Keywords: Ko; horse feed; contaminants; anti-doping; mass spectrometry